ANALISIS TRAINER AIR CONDITIONIG JENIS SPLIT UNTUK MEDIA PEMBELAJARAN: ANALISIS TRAINER AIR CONDITIONING JENIS SPLIT UNTUK MEDIA PEMBELAJARAN - Ardiansyah, Mochammad Syahtia (Jurnal Rekayasa Mesin, 2020)
One of the supporting factors for comfort in the room, namely air conditioning. The principle of air cooling involves a refrigeration cycle, where air is cooled by the refrigerant, then the refrigerant is pressed using a compressor to a certain pressure and the temperature rises, then it is cooled by environmental air so that it melts. The coefficient of performance (COP) is the ratio between the heat absorbed from the cooling room (refrigeration effect) and the work done by the compressor. At the cooling load, the highest pressure and temperature are obtained in the refrigeration system at a load of 350W. The test results obtained based on the temperature and cooling load that have been determined, namely the COP obtained at a load of 350W is , a load of 300W , a load of 250W . For (m) is the rate of refrigerant that has not been obtained. The highest refrigeration effect is at a load of 350W with a value of 177 kJ/kg. 0.384KW. Keyword: Air Conditioning, The priciple of air cooling, COP.